USING ARTIFICIAL INTELLIGENCE TO EVALUATE THE RISKS ASSOCIATED WITH YIELD SHORTAGE - Muhamediyeva, D.T.; Raupova, M. (SCIENCE and SOCIETY, 2025)
The article highlights the emergence of the digital economy and related technologies, which provide many perspectives for working with uncertain data in agriculture. Mainly, the possibilities of using advanced technologies that provide were considered a large amount of information in agricultural conditions to the target agricultural workers.